Stimulation of Articulation for Pre School Age Children with Bibliotherapy - Merina, Nuning Dwi; Eliya, Emi; Khadidi, Khofi (Health Notions, 2018)
Public Speech and language skills are aspects related to the ability to respond the voice, speech, communicate following orders and smooth articulation, stimulation that can be given to the development of articulation and language of preschool age children is bibliotherapy. Bibliotherapy by using the book as a therapy to support the needs of children for development and personal experiences of preschoolers. The purpose of this study was to determine the effect of bibliotherapy on the development of articulation in pre school age children. The design of this study is quasi experimental research with nonequivalent control group pre-test design. The sampling technique used purposive sampling with the minimum sample size of each experimental group and the control group is 20 respondents. Stimulation of this study was given for 3 days with a duration of 40 minutes using Denver Articulation Screening Exam. The result showed p value = 0.000 <Î± = 0.05 in the experimental group and the control group p value 0.743> Î± 0.005. Preschool-aged children that given bibliotherapy have a smooth alteration in articulation pronunciation because the fast mapping process that occurs in their brains, they will quickly absorb the meaning of the newly heard word once or twice, then they quickly make a hypothesis about the meaning of the word and store it in memory. Keywords: Articulation, Bibliotherapy, Preschool age children